Ações de insubordinação criativa na docência de uma educadora matemática - Santos, Patrícia Corrêa (2020)
The present study aimed to identify and analyze, based on the narrative of a Basic Education Mathematics teacher, the movement of creative insubordination actions. Characterized as a political action focused on social justice, on ethical grounds, at first the identification of this action is conditioned to the context and objectives. From these conditions, it was asked: what is revealed in a mathematics teacher's narrative about the movement of creative insubordination actions? A study was carried out on the emergence of the concept in Education and Mathematical Education and a brief analysis of the related concepts, responsible subversion and positive deviation. From the perspective of biographical research, the achievement of the objective relied on a narrative interview as the main methodological instrument in obtaining data from research research based on a model elaborated based on the approach of Fritz Schütze, from which two investigative axes emerged. non-exclusive. With a focus on the dimensions of the movement of creative insubordination actions, the saber: context; professional characteristics and principles; objective and, theme and / or generating phenomena, this study revealed the dynamics of the protagonist's actions, Professor Alice, which converged with the concept of creative insubordination. Teaching autonomy and creativity was highlighted as an emancipatory process in decision-making; moral ethics, social justice and commitment to educational practice as professional principles that legitimize a creative insubordinate stance; and zeal for the other, as well as educational responsibility as one of the characteristics of those who perform a subversively responsible action in their profession. Actions of creative insubordination in teaching are founded on the purpose of offering to the conditions of students, when necessary, so that they learn a more creative mathematics and reduced to the reality of life of these students